2021
DOI: 10.22225/wedj.4.2.2021.68-74
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jumlah Uang Beredar dan Nilai Tukar Rupiah (Kurs) Terhadap Tingkat Inflasi di Indonesia Tahun 2011-2018

Abstract: Penelitian ini bertujuan untuk menguji pengaruh jumlah uang beredar dan nilai tukar rupiah terhadap tingkat inflasi. Metode yang digunakan adalah Analisis regresi linear berganda, koefisien determinasi, uji F dan uji t. hasil output SPSS menunjukkan bahwa secara parsial jumlah uang beredar berpengaruh negatif signifikan terhadap inflasi dan nilai tukar rupiah berpengaruh positif signifikan terhadap tingkat inflasi. Sedangkan secara simultan jumlah uang beredar dan nilai tukar rupiah secara bersama-sama berpeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
2
7
0
9
Order By: Relevance
“…Therefore, it can be concluded that the exchange rate has a significant positive effect on the money supply so this result is proven by the previously assumed hypothesis. The results of this study are consistent with the study by Murad et al (2021), Leasiwal and Subhan (2021), Carissa and Khoirudin (2020), Sean et al (2019), Ningsih and Kristiyatnti (2018), Ichwani and Nisa (2021), Susmiati et al (2021), andAdeshola et al (2020). According to Carissa and Khoirudin (2020), the amount of money in circulation is seen through the supply of money, if the supply of money in a currency increases, the exchange rate will decrease.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, it can be concluded that the exchange rate has a significant positive effect on the money supply so this result is proven by the previously assumed hypothesis. The results of this study are consistent with the study by Murad et al (2021), Leasiwal and Subhan (2021), Carissa and Khoirudin (2020), Sean et al (2019), Ningsih and Kristiyatnti (2018), Ichwani and Nisa (2021), Susmiati et al (2021), andAdeshola et al (2020). According to Carissa and Khoirudin (2020), the amount of money in circulation is seen through the supply of money, if the supply of money in a currency increases, the exchange rate will decrease.…”
Section: Discussionsupporting
confidence: 92%
“…This result is proven by the hypothesis assumed by previous researchers. The results of this study obtained the same results as the research conducted by Susmiati et al (2021), Khanom (2019), Firmansyah (2016), and Jumhur et al (2018. An increase in the money supply will have a major impact on increasing inflation in the country.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations